(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The study deals with one of the most important concepts in human resource management in general and influencing it in a high rate in the case of Iraqi hotels in particular, Where the study touched upon the concepts of organizational justice as an independent variable and the behavior of citizenship as a dependent variable in terms of the nature of the influence relationship between them And with a real management problem inside Iraqi hotels, through which a number of hypothesis were made to measure them And knowing whether there are moral effects on the level of the main and sub variables This study was applied to a group of Iraqi hotels as the study community By designing the questionnaire using a Likert scale and distributing (150) forms to workers in those hotels And then collect data and analyze it statistically using the program (spss v.25)